1984
DOI: 10.1123/jsp.6.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Competence in Soccer Skills among Young Soccer Players

Abstract: Harter's (1979) perceived competence subscale was modified to specifically apply to soccer in order to compare young soccer players' general self-esteem, perceived physical competence, and perceived soccer competence scores in predicting players' actual soccer ability. Young soccer players (N = 217), 8 to 13 years of age, were tested on five soccer skill tests. Players also completed Harter's (1979) Perceived Competence Scale for Children and our perceived soccer competence subscale. We hypothesized that perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
6

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 0 publications
4
18
0
6
Order By: Relevance
“…One construct that has received considerable attention in assessment development and refinement is physical selfconcept, defined as descriptions of attributes and roles of one's physical self (Fox, 1998;Marsh, 1996;Sonstroem, 1997). Historically, measurement of physical selfconcept was primarily unidimensional (e.g., Feltz & Brown, 1984). However, physical selfconcept cannot be properly understood if its multidimensionality is ignored (Marsh & Shavelson, 1985).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…One construct that has received considerable attention in assessment development and refinement is physical selfconcept, defined as descriptions of attributes and roles of one's physical self (Fox, 1998;Marsh, 1996;Sonstroem, 1997). Historically, measurement of physical selfconcept was primarily unidimensional (e.g., Feltz & Brown, 1984). However, physical selfconcept cannot be properly understood if its multidimensionality is ignored (Marsh & Shavelson, 1985).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…228). As a number of authors note, a lack of experience and a lack of ability are by far the most common reasons for students not wanting to participate in sporting activities (Feltz & Brown, 1984;Tjeerdsma, Rink, & Graham, 1996). Having skill correlates with enjoyment, which in turn enhances participation.…”
Section: Resultsmentioning
confidence: 99%
“…Feltz and Brown (1984) and Roberts (1992) found some facts from the athletic activities of soccer and these facts indicated that the extents of the perceptive capabilities of an individual would remarkably affect the performance, skills, learning interest and motivation in soccer. If the instruction could be conducted by using appropriate instructive strategies and methods, it would be highly helpful to enhance the perceptive capabilities of students (György 2014).…”
Section: Competence Motivation Theorymentioning
confidence: 99%
“…The competence motivation theory had been widely explored and applied in the educational fields especially in the assessment on learning interest and motivation (Feltz and Brown 1984;Ommundsen and Vaglum 1991;Roberts 1992;Zou et al 2012). Feltz and Brown (1984) and Roberts (1992) found some facts from the athletic activities of soccer and these facts indicated that the extents of the perceptive capabilities of an individual would remarkably affect the performance, skills, learning interest and motivation in soccer.…”
Section: Competence Motivation Theorymentioning
confidence: 99%